Bank Management, Finance and Sustainability - Aristei, David; Gallo, Manuela (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book comprises a collection of empirical and theoretical studies covering a wide range of themes related to bank management, finance and sustainability. Sustainability represents an opportunity for banks as it contributes to improvements in trust in the banking system. However, sustainable business models must be financially viable so that they can have a positive impact on banks' profitability, stimulating the long-term growth and resilience of the banking industry and overall financial stability.Banks are widely acknowledged as playing a crucial role in achieving the Sustainable Development Goals (SDGs), as they can promote responsible investments and integrate environmental and social criteria into lending and investment strategies. Financial intermediaries can support projects and activities that create a measurable positive economic, social and environmental impact by providing easier access to capital. Furthermore, they can have an active role in improving the financial awareness, inclusion and resilience of the most vulnerable individuals in society.